2017
DOI: 10.1093/ejcts/ezx227
|View full text |Cite
|
Sign up to set email alerts
|

Transapical aortic valve replacement is a safe option in patients with poor left ventricular ejection fraction: results from the Italian Transcatheter Balloon-Expandable Registry (ITER)†

Abstract: TAVI yields good results in patients with depressed LVEF. Age, preoperative creatinine and preoperative pacemaker are independently associated with mortality. The TA access is associated with mortality only after 3 years of follow-up, thus probably reflecting a worse general clinical status of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Postprocedural atrioventricular block requiring a PPM implantation is the main cardiac complication, which has been widely investigated in the currently published researches, 6 , 10 , 20 , 21 with, contrary to our results, an incidence of 13.4% according to a recently published systematic review involving 11,599 patients. 8 Previous published research has consistently found that procedure-related parameters such as the implantation of a larger prosthesis into a smaller annulus and a deep valve implantation, but also patient-related ones included a pre-existing right bundle block, patient age >75 years, male gender, chronic AF, perioperative bradycardia and high calcification load of the native valve are among the main risk factors for postprocedural heart block.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Postprocedural atrioventricular block requiring a PPM implantation is the main cardiac complication, which has been widely investigated in the currently published researches, 6 , 10 , 20 , 21 with, contrary to our results, an incidence of 13.4% according to a recently published systematic review involving 11,599 patients. 8 Previous published research has consistently found that procedure-related parameters such as the implantation of a larger prosthesis into a smaller annulus and a deep valve implantation, but also patient-related ones included a pre-existing right bundle block, patient age >75 years, male gender, chronic AF, perioperative bradycardia and high calcification load of the native valve are among the main risk factors for postprocedural heart block.…”
Section: Discussioncontrasting
confidence: 99%
“…It is estimated that during the 3-year period (2011–2014), more than 26,000 TAVI procedures had been performed at 348 centers in the USA with satisfactory patient outcomes. 5 However, despite the high safety and effectiveness of TAVI procedure in appropriately selected patients groups, 6 this therapeutic option has several periprocedural complications, including stroke, bleeding, vascular complications, acute kidney injury, requirement for permanent pacemaker (PPM) implantation, myocardial infarction, valve malposition, paravalvular leak and heart block. 7 , 8 In the currently available published research, several patient and technical-related factors have been associated with postprocedural complications such as advanced age, female gender, diabetes mellitus, poor left ventricular ejection fraction, peripheral arterial disease, access route, size of the delivery system, history of stroke, prior and/or a new-onset atrial fibrillation (NOAF), baseline severe aortic regurgitation, severity of calcifications on the valve and the aortic arch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found a significant increase of ≥10% in LVEF at discharge, which was persistent at 1-year follow-up. 10 Theoretically, it can be assumed that manipulation of the LV apex will worsen the functioning of an already suffering LV myocardium. Findings from this study, however, does not support this notion.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the belief that the transapical approach was unfit for low-ejection fraction patients. Recently, however, favourable outcomes have been reported even in this particular subsetting [17][18][19]. Left anterior descending (LAD) coronary artery injury can also occur suturing the left ventricular apex; precise identification of the LAD during the procedure by means of direct vision is mandatory to prevent this complication.…”
Section: Transapical Tavrmentioning
confidence: 99%